Pengaruh Persepsi Dukungan Organisasi dan Kompetensi pada Kinerja Karyawan Dimediasi Komitmen Afektif - Murniasih, Emi; Sudarma, Ketut (Universitas Negeri Semarang, 2016)
The purpose of this study was to examine the effect of perceived organizational support and competency to employee performance mediated by affective commitment. The population of the study was inpatient nurses of RSUD dr. H. Soewondo Kendal totaling 108 peoples. Sampling using Non-probability Sampling technique saturated sampling. The results showed positive significant effect perceived organizational support and competency on employee performance. Affective commitment also proved mediating perceived organizational support and competency on employee performance showed by coefficient total value of perceived organizational support on employee performance (0,371) > direct effect value (0,243) and coefficient total value of competency on employee performance (0,401) > direct effect value (0,242).